2018
DOI: 10.5114/pjp.2018.81696
|View full text |Cite
|
Sign up to set email alerts
|

Histological heterogeneity and distributional difference of gastric carcinosarcoma: report of 4 cases and literature review

Abstract: Carcinosarcoma is a rare malignant neoplasm, consisting of both epithelial and mesenchymal component. Primary gastric carcinosarcoma is rare and poorly understood. We reported clinicopathologic features of 4 cases and analysis of 76 cases published in the literature. Clinical symptoms were nonspecific with epigastric pain, weight loss, and melena, as the most common complaints. The prognosis of patients was dismal with high mortality. The tumor commonly occurred in the upper stomach in Chinese patients, wherea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 44 publications
(51 reference statements)
1
18
0
Order By: Relevance
“…from Japan [9,10]. An evaluation of the sarcomatous component showed that sarcomas in 8 out of 76 cases contained at least 2 ectopic component types, and 2 cases contained 3 ectopic component types [3]. In the present case, we observed a unique histology, including more independently differentiated regions than in those reported in the literature.…”
Section: Reports Of Cases That Include An Afp-producing Gastric Carcisupporting
confidence: 51%
See 1 more Smart Citation
“…from Japan [9,10]. An evaluation of the sarcomatous component showed that sarcomas in 8 out of 76 cases contained at least 2 ectopic component types, and 2 cases contained 3 ectopic component types [3]. In the present case, we observed a unique histology, including more independently differentiated regions than in those reported in the literature.…”
Section: Reports Of Cases That Include An Afp-producing Gastric Carcisupporting
confidence: 51%
“…In general, for the histological findings of gastric carcinosarcoma, the carcinomatous and sarcomatous components are predominantly adenocarcinomatous and undifferentiated sarcoma, respectively. Of the 76 cases of gastric carcinosarcoma found in a literature review by Nie et al, 4 were adenosquamous carcinomas, and 7 were neuroendocrine carcinomas [3].…”
Section: Discussionmentioning
confidence: 96%
“…In general, for the histological ndings of gastric carcinosarcoma, the carcinomatous and sarcomatous components are predominantly adenocarcinomatous and undifferentiated sarcoma, respectively. Of the 76 cases of gastric carcinosarcoma found in a literature review by Nie et al, 4 were adenosquamous carcinomas, and 7 were neuroendocrine carcinomas [3]. Reports of cases that include an AFP-producing gastric carcinoma component are limited to 2 cases from Japan [9,10].…”
Section: Discussionmentioning
confidence: 99%
“…The resected gastric tumor was subjected to histopathological examination. Macroscopically, the gastrectomy specimen had a protruding lesion measuring 41 × 29 × 18 mm 3 (Fig. 1b).…”
Section: Case Presentationmentioning
confidence: 99%
See 1 more Smart Citation